MODELO DE NEGÓCIO NA EDUCAÇÃO SUPERIOR A DISTÂNCIA: UMA PESQUISA EXPLORATÓRIA DAS TENDÊNCIAS E APROXIMAÇÕES COM O FREEMIUM - MORGAN, SILVIA MARIA MORETTI (2016)
The distance education in Brazil has undergone significant changes in recent years. These changes end up awakening, especially in managers, the search and implementation of new business models for the offering and distribution of content produced emphasizing this mode as easing the provision of higher education in the country.Bekkelund (2011) in his study "Succeding with freemium" suggested a set of eight propositions that should be used as guidance for companies wishing to employ freemium as a business model.The guiding question of this dissertation is: The business model of distance education have been influenced by changes in progress in the creative industry? The overall objective of this study is is to identify possible trends of changes in business models of Distance Education by means of exploratory research of a quantitative nature. This is a quantitative research study with the scale proposed application by Bekkelund via survey. The results show that there are features of replicable freemium business models in the context of business management model oriented for distance education.